Pendidikan Humanisme dalam Pembentukan Karakter Peserta Didik: Perspektif Pemikiran KH. Abdurrahman Wahid - Tanti Sulastini (CV. Biha Cendekia, 2026)
Technological developments and social changes often lead to the emergence of individualistic attitudes, a decline in social empathy, and a reduced appreciation for human values. Therefore, an educational concept is needed that is capable of instilling humanistic values in the formation of students’ character, one of which can be found in the thoughts of KH. Abdurrahman Wahid (Gus Dur). This study aims to analyze the concept of humanistic education in shaping students’ character based on Gus Dur’s perspective. The research method used is a qualitative approach with a library research design. Data sources were obtained from various literatures related to Gus Dur’s thoughts, humanistic education, and other relevant academic studies. Data were collected through documentation studies, while the analysis employed content analysis techniques. The results show that Gus Dur’s concept of humanistic education is based on monotheistic humanism (tauhid-based humanism) that integrates divine values with human values. This concept is reflected in three main principles: Islamic universalism, Islamic cosmopolitanism, and the indigenization of Islam. Islamic universalism emphasizes the protection of fundamental human rights, Islamic cosmopolitanism encourages openness to global knowledge, while the indigenization of Islam highlights the contextualization of Islamic teachings within local culture. The implementation of this concept in education can be carried out through the integration of religious and general education, the habituation of social values, and the strengthening of character education based on humanistic ethics. Thus, humanistic education from Gus Dur’s perspective remains relevant in shaping students who are morally grounded, humanistic, tolerant, and civilized.